Pembaharuan Pengaturan Pemulihan Hak Korban Dalam Kasus Salah Tembak Oleh Petugas Kepolisian Republik Indonesia Dikaitkan Dengan Hak Korban - M. Fandi Bachtiar; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Police Officers have the right to shoot the perpetrators of criminal acts, but those rights are often misused or negligent in their implementation causing innocent people to be victims. Victims of shootings by police officers have the right to get a restoration of their rights. The purpose of this essay is to know the mechanism of restoring the right of victims of shoot by the Police Officers of the Republic of Indonesia, to know the obstacles in restoring the right of victims of shoot by the police officers of the Republic of Indonesia. To know the effort to renew the regulation on the recovery of the right of victims of shoot by the officers of the Police of the Republic of Indonesia. This type of research can be classified in the type of normative research (legal research) or also called bibliography research, ie research conducted with normative juridical approaches studied are library materials or secondary data, which consists of primary legal materials, secondary law materials, and legal materials tertiary. Data collection techniques used in the writing of this research is to use literature review method or documentary study. From the research results, there are three things that can be concluded. First, the recovery mechanism of victims' right to shoot is complicated. The number of requirements and the flow of procedures that the victim must face, Secondly, the obstacles in restoring the right of victims of the shoot are quite a lot because the recovery mechanism has not been in accordance with the mandate of Amendment II of the 1945 Constitution and the principles that must be considered in the recovery of victims' rights. Third, Efforts to update the regulation on the recovery of victims' right to shoot were done by revising the Decree of the Minister of Finance No. 983 / KMK.01 / 1983 on the Procedure of Payment of Indemnification, establishing new institutions or granting additional authority to LPSK or KOMPOLNAS in order to conduct investigations on Police Commit a crime, Replace or revise Law Number 31 Year 2014 on the Protection of Witnesses and Victims. Suggestion of the writer, First, In recovering the right of victims of shoot, the Government is expected to pay more attention to the principles that guide the recovery of victims' rights and legal regulations especially the Amendment II of the 1945 Constitution. Second, establishing new institutions or providing additional authority to existing institutions such as LPSK or KOMPOLNAS Institute in order to conduct investigations and investigations of police officers who commit criminal acts. This is done because police law enforcement officers tend not to be neutral and transparent. Evidenced by the still many cases do not go to trial. This hampers the process of recovering the rights of victims as regulated in the Criminal Procedure Code. Third, Establish a new law or revise the Law on the restoration of the rights of victims. Key words : Recovery of Victim's Rights - Wrong Shoot - Police Office